2018
DOI: 10.1007/978-3-319-73951-9_16
|View full text |Cite
|
Sign up to set email alerts
|

Emerging from the Cloud: A Bibliometric Analysis of Cloud Forensics Studies

Abstract: Emergence of cloud computing technologies have changed the way we store, retrieve, and archive our data. With the promise of unlimited, reliable and always-available storage, a lot of private and confidential data are now stored on different cloud platforms. Being such a gold mine of data, cloud platforms are among the most valuable targets for attackers. Therefore, many forensics investigators have tried to develop tools, tactics and procedures to collect, preserve, analyse and report evidences of attackers' … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 48 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…An analysis of the literature on gunshot residue was reported by Sobreira et al which focused on keywords and cross citation in addition to co-authorship and countries of origin to determine research trends and the evolution of the research base (Sobreira et al, 2020). Finally, with the growing user presence on digital platforms, studies summarizing the current research trends in digital forensics have been reported for digital imaging (Baldwin et al, 2018) and cloud forensics (Gokhale et al, 2020).…”
mentioning
confidence: 99%
“…An analysis of the literature on gunshot residue was reported by Sobreira et al which focused on keywords and cross citation in addition to co-authorship and countries of origin to determine research trends and the evolution of the research base (Sobreira et al, 2020). Finally, with the growing user presence on digital platforms, studies summarizing the current research trends in digital forensics have been reported for digital imaging (Baldwin et al, 2018) and cloud forensics (Gokhale et al, 2020).…”
mentioning
confidence: 99%
“…Consequently, we have applied bibliometric and social network analysis (SNA) techniques (Borgatti et al 2013;Spinak 1996) to identify the mechanisms of knowledge production. Such techniques have previously been used in crime-related research, for example, to describe cloud forensics research trends (Baldwin et al 2018), human trafficking research trends (Sweileh 2018) or the author communities associated to the Evolution of the Environmental Criminology and Crime Analysis (ECCA) Symposiums (Bichler and Malm 2008). However, as far as we are aware, this is their first use in the analysis of CPTED research and time-lines.…”
Section: Introduction and Aimmentioning
confidence: 99%
“… The Cyber Threat Intelligence Centre (CTI) offers data to cyber security technologies in order to assist those tools in better understanding the dangers that require attention as well as the strategies, methods, and procedures (TTP) that may be utilized to mitigate such threats [29].  CTI makes available knowledge that can assist security analysts and IT operations teams in the development of security strategies and the swift implementation of such plans in order to defend networks from serious attacks [30].…”
Section: Need Of Ctimentioning
confidence: 99%